2D coordination polymer-derived CoSe2–NiSe2/CN nanosheets: the dual-phase synergistic effect and ultrathin structure to enhance the hydrogen evolution reaction. Issue 28 (5th July 2021) - Jiang, Weifeng; Sun, Jianpeng; Lu, Kebin; Jiang, Chuanhai; Xu, Huakai; Huang, Zhaodi; Cao, Ning; Dai, Fangna
Abstract : A two-step method to synthesize 2D ultrathin dual-phase composites (CoSe2 –NiSe2 /CN) with large specific surface area, abundant catalytically active sites and synergistic effects which can significantly enhance the catalytic activity of the HER. Abstract : The evolution of cost-effective hydrogen evolution reaction (HER) electrocatalysts is of great significance for the development of clean energy. Exploring effective synthesis strategies to optimize the performance of non-noble metal electrocatalysts has always attracted our attention. Herein, ultrathin coordination polymers were used as precursors to controllably synthesize two-dimensional (2D) ultrathin dual-phase transition metal selenide (TMSs)/carbon–nitrogen (CN) composites (CoSe2 –NiSe2 /CN) by a two-step method (first a low temperature hydrothermal method for selenization, and then high temperature calcination selenization). Benefiting from its large specific surface area (49 m 2 g −1 ), abundant catalytically active sites and synergistic effects, CoSe2 –NiSe2 /CN can significantly enhance the HER catalytic activity and exhibits good electrocatalytic activity with an overpotential of 150 mV at −10 mA cm −2, and a small Tafel slope of 42 mV dec −1 in an acidic electrolyte for the HER. This work provides a new strategy for optimizing the HER catalytic activity of TMSs by preparing 2D ultrathin dual-phase TMS composite materials.